A Note on Profit Maximisation and its Implications - Scitovszky, T. De (Review of Economic Studies, 1943)
A Note on Profit Maximisation and its Implications Get access T. de Scitovszky T. de Scitovszky Stillwater, Oklahoma Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 11, Issue 1, Winter 1943, Pages 57–60, https://doi.org/10.2307/2967520 Published: 01 December 1943